2020
DOI: 10.1080/2162402x.2020.1746113
|View full text |Cite
|
Sign up to set email alerts
|

Liver metastases and the efficacy of the PD-1 or PD-L1 inhibitors in cancer: a meta-analysis of randomized controlled trials

Abstract: Objective: To explore the relations between liver metastases (LM) and the efficacy of the treatments with programmed cell death 1 (PD-1) or programmed cell death ligand 1 (PD-L1) inhibitors. Method: Pubmed, Embase, American Society of Clinical Oncology and the European Society for Medical Oncology were searched to select eligible studies about PD-1 or PD-L1 inhibitors (Nivolumab, Pembrolizumab, Cemiplimab, Avelumab, Durvalumab, and Atezolizumab). We included only the original randomized controlled trials (RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…In our study, a higher PD-L1 level in liver metastases suggested that PD-L1 expression might also be involved in liver tolerance. However, combining the relative resistance to PD-1/PD-L1 inhibitors in patients with liver metastasis, we proposed that the ability of PD-1/PD-L1 inhibitors to enhance the immune system's response may be partially counteracted by other mechanisms of liver tolerance, thus compromise the effectiveness of treatment [27].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a higher PD-L1 level in liver metastases suggested that PD-L1 expression might also be involved in liver tolerance. However, combining the relative resistance to PD-1/PD-L1 inhibitors in patients with liver metastasis, we proposed that the ability of PD-1/PD-L1 inhibitors to enhance the immune system's response may be partially counteracted by other mechanisms of liver tolerance, thus compromise the effectiveness of treatment [27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who develop liver metastases have been found to have poorer outcomes than those with metastases to other sites, 23 and monoimmunotherapies and chemotherapies have mostly been ineffective in these patients. [24][25][26] In a previous study, patients with baseline liver metastases were found to have improved OS with bevacizumab plus carboplatin and paclitaxel. 9 Therefore, we hypothesized that the poor treatment outcomes with immunotherapy in patients with liver metastases could be attributed to tissue-specific immunoregulation, which might be reversed by combination treatment with bevacizumab.…”
Section: Introductionmentioning
confidence: 95%
“…However, CD8 + T cell counts in the liver were lower compared to non-liver metastatic sites, which might contribute to the higher immune tolerance of the liver. 127,128 Therefore, combinational therapies targeting the immune system might be of added value specifically in the liver. As TGF-β shows a clear immune suppressive role, inhibition of TGF-β might elevate this suppression, and combining this inhibition with immunotherapy might improve the response rate of immunotherapy.…”
Section: Combining Tgf-β Inhibitors and Immunotherapymentioning
confidence: 99%